2002
DOI: 10.1099/0022-1317-83-6-1325
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of a novel gammaherpesvirus isolated from a European badger (Meles meles)

Abstract: A herpesvirus causing a cytopathic effect was isolated from pulmonary fibroblast cultures established from a European badger (Meles meles).A study was undertaken to classify and to assess some in-vitro growth characteristics of this virus. From a panel of 27 mammalian cell lines, in-vitro replication of the badger herpesvirus (BadHV) was only demonstrated with a mink lung cell line, suggesting a high degree of host specificity. Using PCR with degenerate primers, three independent fragments of the BadHV genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…In our initial analysis, 4 of 60 domestic cat samples were PCR positive, and 453-bp gB sequences amplified from these samples were identical ( Table 2). Comparison of this sequence to sequences in GenBank by BLAST analysis demonstrated homology to GHV gB sequences from other species, with the greatest similarity (80% nucleotide identity) being to mustelid herpesvirus 1 (MusHV1) of European badgers (36). The presence of this novel GHV sequence in multiple cats provided evidence for the likely existence of a novel GHV in cats.…”
Section: Resultsmentioning
confidence: 83%
“…In our initial analysis, 4 of 60 domestic cat samples were PCR positive, and 453-bp gB sequences amplified from these samples were identical ( Table 2). Comparison of this sequence to sequences in GenBank by BLAST analysis demonstrated homology to GHV gB sequences from other species, with the greatest similarity (80% nucleotide identity) being to mustelid herpesvirus 1 (MusHV1) of European badgers (36). The presence of this novel GHV sequence in multiple cats provided evidence for the likely existence of a novel GHV in cats.…”
Section: Resultsmentioning
confidence: 83%
“…Mustelid herpesvirus-1 (MusHV-1) is a newly described herpesvirus isolated from a primary pulmonary cell culture derived from a European badger (Meles meles) in Cornwall, England (Banks et al, 2002). Phylogenetic analysis of sequence data demonstrates that MusHV-1 is a novel member of the Rhadinovirus genus within the Gammaherpesvirinae closely related to equine herpesvirus-2 and -5.…”
mentioning
confidence: 99%
“…2,4,7,8 The fetal mink lung (ML) epithelial cell line g was also used because it is derived from a member of the Mustelidae family. 1 Ten-day-old embryonated eggs h (inoculated into the chorioallantoic sac and the chorioallantoic membrane) were also used for virus isolation.…”
mentioning
confidence: 99%
“…Nucleotide comparison showed that the nearest nt homology was with the viral DNA polymerase (DPOL) gene of Mustelid herpesvirus 1 (MusHV-1; also known as Badger herpesvirus; order Herpesvirales, family Herpesviridae, subfamily Gammaherpesvirinae, genus Percavirus). 1 The Fisher herpesvirus (FiHV) partial sequence possesses 85.3% nt identity and 91.7% aa identity with the MusHV-1 DPOL gene published sequence (Fig. 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation